Newly Developed Polyglycolic Acid Reinforcement Unified with Sodium Alginate to Prevent Adhesion. (3rd April 2018) - Morita, Shinichiro; Takagi, Toshitaka; Abe, Rie; Tsujimoto, Hiroyuki; Ozamoto, Yuki; Torii, Hiroko; Hagiwara, Akeo
Abstract : Polyglycolic acid (PGA) mesh fabric is widely used for reinforcing injured tissues during surgeries. However, PGA induces chronic inflammation and adhesion. The purpose of this study is to develop PGA reinforcement "without PGA-induced adhesion." We developed a reinforcement fabric unified with PGA mesh and alginate foam. The antiadhesive effects of sodium alginate foam and calcium alginate foam were evaluated in rats. Sodium alginate foam unified with PGA mesh fabric exhibited strong effects that limit the extent and severity of adhesion, whereas calcium alginate foam unified with PGA mesh was less effective in preventing adhesion. In the sodium alginate group, fibroblasts and collagen fibers around implanted sites were sparse and the material degraded rapidly by macrophage ingestion. Fibroblasts and collagen fibers play a major role in adhesion formation and their excessive proliferation results in postoperative adhesion. Thus, inhibiting their increase is the key in preventing PGA-induced adhesion. The reinforcement that is composed of PGA mesh unified with sodium alginate foam strongly inhibited PGA-induced adhesion and showed excellent handling during surgery and could be easily applied with a one-step procedure.